Long-Lasting Exendin-4 Fusion Protein Improves Memory Deficits in High-Fat Diet/Streptozotocin-Induced Diabetic Mice - Park, Kyung-Ah (Pharmaceutics, 2020)
Glucagon-like peptide 1 (GLP-1) mimetics have been approved as an adjunct therapy for glycemic control in type 2 diabetic patients for the increased insulin secretion under hyperglycemic conditions. Recently, it is reported that such agents elicit neuroprotective effects against diabetes-associated cognitive decline. However, there is an issue of poor compliance by multiple daily subcutaneous injections for sufficient glycemic control due to their short duration, and neuroprotective actions were not fully studied, yet. In this study, using the prepared exendin-4 fusion protein agent, we investigated the pharmacokinetic profile and the role of this GLP-1 mimetics on memory deficits in a high-fat diet (HFD)/streptozotocin (STZ) mouse model of type 2 diabetic mellitus. After induction of diabetes, mice were administered weekly by intraperitoneal injection of GLP-1 mimetics for 6 weeks. This treatment reversed HFD/STZ-induced metabolic symptoms of increased body weight, hyperglycemia, and hepatic steatosis. Furthermore, the impaired cognitive performance of diabetic mice was significantly reversed by GLP-1 mimetics. GLP-1 mimetic treatment also reversed decreases in GLP-1/GLP-1 receptor expression levels in both the pancreas and hippocampus of diabetic mice; increases in hippocampal inflammation, mitochondrial fission, and calcium-binding protein levels were also reversed. These findings suggest that GLP-1 mimetics are promising agents for both diabetes and neurodegenerative diseases that are associated with increased GLP-1 expression in the brain.